ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA (ADD): Studi Kasus Pada Desa Wewit Kecamatan Adonara Tengah Kabupaten Flores Timur - Burhаn, Sunаrti; Sayang, Sabulon; Reo, Hermanus (Program Studi Akuntansi Universitas Flores, 2025)
This studi aims to analyze accountability and transparency in menagging vilage fund allocations in Wewit Vilage, Central Adonara District, East Flores Regency. This research is a qualitative descriptive study using primary and secondary data as the type and source of the data. Data collection techniques in the form od interviews and dosumentation. Data analysis techniques include data collection, data reduction, data presentation, as well as conclusions and verification. The result of this study indicate that accountability in Wewit Village is accountavle and in accordance with Permendagri number 20 of 208. Wewit Village has informed the APBDesa in the form of billboards that the local community can see directly. However, there are no billboards indicating which activities have been carried out or which have not been carried out. Wewit Village has also not provived APBDesa information on the villages's official website and there is no recording of incoming and outgoing cash on the onformastion board so that it cannot be accessed easily by the community. So, Wewit Village has not fully implemented the transparency system and is not in accordance with Permendagri No. 20 of 2018. So there needs to be improvement and further guidance to creare good village governace in West Village, Central Adonara District, East Flores Regency.